PENGARUH MEDIA PEMBELAJARAN E-LEARNING TERHADAP PRESTASI BELAJAR SISWA MADRASAH IBTIDAIYAH AL-BAROKAH PATIANROWO NGANJUK - Ani Zulfah, Machnunah; Fakhril Imami, Nada (JoEMS (Journal of Education and Management Studies), 2021)
The purpose of this study is to find out the influence of Online Learning on the Achievement of The Results of The Study of high-class students in MI Al-Barokah Patianrowo Kab. Nganjuk school year 2020/2021. This study uses quantitative method with data test using spss 16. The data of this study was obtained through the filling of questionnaires by students, recap nila pts, as well as conducted interviews by teachers of fiqh subjects, and the principal of MI Al-Barokah Patianrowo Nganjuk as supporting data. The tests are validity, reliability, and Z test to find out how much influence online learning has on students' learning outcomes. The results showed that online learning with e-learning media has a specific influence on the achievement of learning outcomes as much as the average pretest score of 75 for posttest scores get a score of 86. From the results of the spss test that the results of the analysis using Z test paired get a significant score of 0.000consultative 0.05 so it can be said that there is an influence on the use of e-learning learning media on the prestai student learning outcomes. Online learning can be an alternative world of education in the period of Panemi Covid-19. According to the interviewee, students' learning achievement tends to be stable and does not decrease even though online learning is considered a little more difficult to accept due to several factors both technical and non-technical.